Determinants of dividend payout of Indian manufacturing companies: A quantile regression approach. Issue 4 (8th October 2018) - Thakur, Bhanu Pratap Singh; Kannadhasan, M.
Abstract : Purpose: The purpose of this study is to examine the influence of firm characteristics such as profitability, growth opportunities, size, leverage and maturity on dividend policy of Indian firms. Design/methodology/approach: The study analyzes the determinants of dividend policy of manufacturing firms in India using panel data. Because of the non-linearity behaviour of dividend pay-out by firms, the study uses quantile regression method to examine whether the determinants of dividends vary depending on the company's level of dividends. Findings: Overall, the results show important difference between ordinary least square and quantile regression estimates and depict differential effect on dividend at different levels. The notable difference occurs because either the significance changes (e.g. for profitability and growth opportunities) or because the magnitude of coefficients changes (e.g. for size, profitability and growth opportunities). Originality/value: This finding is useful in identifying the dividend issuing companies. Further, results of this study would be helpful to the mangers to manage their financial positions that subsequently help in retaining and attracting the probable investors.